PEMERIKSAAN KESEHATAN GRATIS PADA MASYARAKAT DESA MARIORIAJA KECAMATAN MARIORIWAWO KABUPATEN SOPPENG - Anggeraeni, Anggeraeni; Nurafriani, Nurafriani; Nurhardianti, Nurhardianti; Hasifah, Hasifah; Sapriana, Sapriana; A, Alfiah; Asiah, Nur (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
The purpose of the extension activities involving the Marioriwawo village community is to get an overview of non-communicable diseases through free health checks. While the targets to be achieved are checking blood pressure, cholesterol, blood sugar and uric acid which is a form of intervention for non-communicable disease health problems. Thus it is very necessary to have free health checks on a regular basis. The activity method used is through Community Empowerment Learning which is a strategic solution for partners by providing free health checks. The activity plan that will be proposed in this community service program: 1) free health checks. 2) counseling at posyandu. 3) Scheduling health check-up activities in schools for teenagers. 4) Evaluation of community service programs.